Recent Developments in Building Diagnosis Techniques - Delgado, João M.P.Q (Building Pathology and Rehabilitation, 2016)
This book presents a collection of recent research on building diagnosis techniques related to construction pathology, hygrothermal behavior and durability, and diagnostic techniques. It highlights recent advances and new developments in the field of building physics, building anomalies in materials and components, new techniques for improved energy efficiency analysis, and diagnosis techniques such as infrared thermography. This book will be of interest to a wide readership of professionals, scientists, students, practitioners, and lecturers.